Pengaruh Ekuitas Merek, Kualitas Layanan, Kualitas Produk, dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Di Starbucks Merr Surabaya - Zahra, Kinanti Almaska; Winarmo, Sri Tjondro; Yuliati, Nuriah (Universitas Hamzanwadi, 2024)
Increasing consumption and lifestyle make coffee one of the trendsetters in society and accelerate competition between coffee shops. The entrepreneurs are charged with creating new innovations to attract customers' interest in buying. Brand equity, service quality, product quality, and costumer satisfaction are amonggthe factors that potentially influence customer loyalty when purchasing coffee drinks. The study aimsgto analyze the impact of brand equity, quality offservice, product qualities, and customerrsatisfaction on customerrloyalty at Starbucksscoffee shop in Surabaya. The research data were analyzed utilizing the SEM-PLS method with the WarpPLS 7.0 software. The primary data wereegathered using questionnairessand interviews with a sample. The primary data were gathered using questionnairessand interviews with aasample of 95 respondents taken using accidental samplinggtechnique. Research results show that brand equity, service quality, product quality, and costumer satisfaction are positively and significantly linked to customer loyalty